Historical aspects and modern surgical approach of patients with anal sphincter incompetence - C. A. Frolov; A. Yu. Titov; N. N. Poletov; I. S. Anosov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. Assessment of optimum surgical method for organic incompetence of anal sphincter (US).Summary. Review of literature demonstrates significance of fecal incontinence issue, as well as the history of operative treatment of anal incontinence, its advantage and shortcomings. The variety of surgical methods used in global practice reflects absence of clear concept of preferable and most effective surgical intervention.Results. Both fundamental and modern data of Russian and foreign studies on application of various surgical techniques for anal incontinence were used at review. The analysis of efficacy of proposed surgical interventions as well as comparative analysis of both early and late postoperative complications was carried out.Conclusion. Treatment of anal incontinence is significant challenge with no established optimal tactics, that requires further development and introduction of new effective methods of surgical treatment.